Plasma levels of VIP are not elevated during PACAP- and VIP-induced cluster headache attacks: an exploratory study - Deligianni, Christina; Pellesi, Lanfranco; Chaudhry, Basit Ali; Haulund Vollesen, Anne Luise; Snoer, Agneta Henriette; Hannibal, Jens; Jensen, Rigmor Højland; Ashina, Messoud (Frontiers in Neurology, 2023)
Background Pituitary adenylate cyclase-activating peptide (PACAP) and vasoactive intestinal peptide (VIP) provoked cluster headache attacks in individuals with episodic cluster headache during their active phase and individuals with chronic cluster headache. In this study, we investigated whether infusions of PACAP and VIP caused alterations in plasma levels of VIP and their potential contribution to induced cluster headache attacks. Methods Participants received either PACAP or VIP infusion for 20 min on 2 separate days with an interval of at least 7 days in between. Blood collection was performed at T0, T20, T30, and T90. Plasma levels of VIP were measured using a validated radioimmunoassay method. Results Blood samples were collected from participants with episodic cluster headache in the active phase (eCHA, n = 14), remission (eCHR, n = 15), and from participants with chronic cluster headache (cCH, n = 15). Baseline levels of VIP did not differ among the three groups (p = 0.1161). During PACAP infusion, mixed-effects analysis revealed a significant increase in plasma levels of VIP in eCHA (p = 0.0300) and eCHR (p = 0.0058) but not in cCH (p = 0.2930). We found no difference in the increase of plasma VIP levels between patients who developed PACAP38- or VIP-induced attacks. Conclusion Cluster headache attacks induced by PACAP38 or VIP infusion are not associated with changes in plasma levels of VIP. Further studies are needed to investigate the role of VIP and the parasympathetic system in cluster headache. Clinical trial registration The parent study is registered at ClinicalTrials.gov (NCT03814226).